Karakter Agronomi dan Toleransi Varietas Cabai Merah Akibat Genangan pada Fase Generatif - Susilawati Susilawati; Rujito Agus Suwignyo; Munandar Munandar; Mery Hasmeda (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Susilawati et al., 2012. Agronomic Characteristics and Tolerance of Red Chili Varieties under Water Logging Stress during Generative Phases. JLSO 1(1):22-30.The research objective was to evaluate the responses of growth and tolerance of red chilli under waterlogging stress during generative phases. Experiments were conducted in village Alang-alang Lebar Palembang, South Sumatra, from April to November 2010. Experimental design used was split plot with three replications. The main plot was waterlogging for 1, 2, 3 and 4 days. The subplot was red chili varieties consisted of Kiyo F1, Bravo F1, Taro F1, Lembang 1, Laris, Riawan, Mario and Kusuma. The results showed that the maximum period of waterlogging of Red chilli plants in the generative phase was three days. Increased duration of waterloggingduring the generative phase significantly decreased the ability of plants to survive, the number of live plants, plant height and the number of branches. Based on the agronomic characteristics found in the study, the variety that is the most tolerant to waterlogging during the generative phase was Kiyo F1.